ANALISIS PROGRAM KESELAMATAN DAN KESEHATAN KERJA DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN PADA DEPARTEMEN FACILITIES MANAJEMEN PT. FREEPORT INDONESIA KABUPATEN MIMIKA PAPUA - Habel Taime; Alfrida Abi (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2022)
Target of research are as folowing: To know what is by together there are influence between Working Safety variable (X1) and Health of Job (X2) to Performance Employees (Y) at Department of Facilities Management of PT. Freeport Indonesia of Timika Papua. Technique intake of sampel weared in this research of writer use technique of Random Sampling. Where each; every population member have is same opportunity to be selected as sampel. From result analyse that there is positive influence of Working Safety variable (X1) to Performance Employees (Y) with value of parsial equal to 0,917 or 84.1% meaning there is very strong influence. Matter in proving with Working Safety variable hypothesis test (X1) to Performance Employees (Y) obtained by value of to = 6,708 > t0,05 (142) = 1,656, hence Ho refused and Is ha accepted to mean there is influence isn't it. From result analyse that there is positive influence [of] variable Health of Job (X2) to Performance Employees (Y) assess correlation of parsial equal to 0,944 or 89,1% meaning there is very strong influence. Matter in proving with hypothesis test between variable Health of Job (X2) to Performance Employees (Y) obtained by value of to = 11,347 > t0,05 (142) 1,656, hence Ho refused and Is ha accepted to mean there is influence isn't it. By Simultan there is positive influence of Working Safety variable (X1) and Health of Job (X2) to Performance Employees variable (Y) obtained [by] correlation value of R equal to 0,958 and while value of R Square equal to 0,917 or 91,7%, this matter can be expressed that result analyse by together Working Safety variable (X1), and Health of Job to Performance Employees variable (Y) have very strong influence. Proved with test of FCount in obtaining value equal to 779,197 where bigger than Ftable (143) equal to 2,670 with level isn't it equal to 0,000 because 0,000 < 0,05, hence by simultan can be told by Working Safety variable (X1) and Health of Job (X2) to Performance Employees (Y) have an effect on isn't it.